How to start and operate your own home-based business - Liatsos, Helene K.; Rarey, Ondine; Home Office Management Experts (Firm) ([Tarzana, Calif.] : Home Office Management Experts, 2006)
This explains how to maximize success and minimize frustration in developing a home-based business
Title from container
Camera, Jonathan Skurnick ; Sound, Josh Wilkenson ; editor/graphics, Ondine Rarey
DVD format
Keywords: Home-based businesses; Small business